Prevalence of temporomandibular disorders in Chennai population - Arvind Muthukrishnan; Gowri Shankar Sekar (Wolters Kluwer Medknow Publications, 2015)
Objective: This study aimed to determine the prevalence of temporomandibular disorders (TMDs) in Chennai city population. Materials and Methods: To obtain a representative sample, a house-to-house survey was conducted in three zones of Chennai and a total of 4197 individuals were randomly selected for the study. Among 4197 individuals, 1158 were excluded from the study, based on the exclusion criteria. Finally, a total of 3039 individuals were included in the study population. Results: More than half of the study sample (53.7%) in the present study had one or more clinical signs and symptoms of TMD. Deviation of mandible on mouth opening (42.1%) and clicking sound (38.6%) made up the highest percentage. Females aged 18 years and older reported higher prevalence of TMD signs and symptoms than men. However, these differences were not significant for all signs and symptoms in all age groups. Prevalence of TMD was reported in this study according to the Research Diagnostic Criteria for Temporomandibular Disorders (RDC/TMD) system of classification, and myofacial pain dysfunction syndrome (MPDS) was reported in 0.8% of the population, internal derangement in 38.3%, and osteoarthritis in 14.6% of the population. Conclusion: Our study, in comparison to other prevalence studies, had a higher sample size and was representative of a cross section of the population. The results of this study show that a significant percentage of the population has signs of TMDs and there are chances that they may develop symptoms of TMDs. Further studies are needed for early identification and initiation of preventive measures which could prevent TMDs progressing to advanced stages where management becomes difficult.